PENGARUH PANTANG MAKANAN TERHADAP KESEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM - Neny Yuli Susanti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2015)
Abstinence food habits is very harmful for the mother postpartum particularly for healing perenium wound. The purpose of this study was to determine the effect of food Abstinence against healing perineal wound process in Private Practice Midwife BPS Hj.Sulis Setyowati, S.ST Asembagus Situbondo. The method used the instrument Comparative Analysis with interview guides and observation sheet. Subjects in this study were post partum mothers who suffered second-degree perineal wound. The sample in this study amounted to 12 people, with a total sampling technique. Further processing of the data using statistical tests